Multifunctional Hyperbolic Nanogroove Metasurface for Submolecular Detection. Issue 30 (8th June 2017) - Jiang, Li; Zeng, Shuwen; Xu, Zhengji; Ouyang, Qingling; Zhang, Dao‐Hua; Chong, Peter Han Joo; Coquet, Philippe; He, Sailing; Yong, Ken‐Tye
Abstract : Metasurface serves as a promising plasmonic sensing platform for engineering the enhanced light–matter interactions. Here, a hyperbolic metasurface with the nanogroove structure in the subwavelength scale is designed. This metasurface is able to modify the wavefront and wavelength of surface plasmon wave with the variation of the nanogroove width or periodicity. At the specific optical frequency, surface plasmon polaritons are tightly confined and propagated with a diffraction‐free feature due to the epsilon‐near‐zero effect. Most importantly, the groove hyperbolic metasurface can enhance the plasmonic sensing with an ultrahigh phase sensitivity of 30 373 deg RIU −1 and Goos–Hänchen shift sensitivity of 10.134 mm RIU −1 . The detection resolution for refractive index change of glycerol solution is achieved as 10 −8 RIU based on the phase measurement. The detection limit of bovine serum albumin (BSA) molecule is measured as low as 0.1 × 10 −18 m (1 × 10 −19 mol L −1 ), which corresponds to a submolecular detection level (0.13 BSA mm −2 ). As for low‐weight biotin molecule, the detection limit is estimated below 1 × 10 −15 m (1 × 10 −15 mol L −1, 1300 biotin mm −2 ). This enhanced plasmonic sensing performance is two orders of magnitude higher than those with current state‐of‐art plasmonic metamaterials and metasurfaces. Abstract : A hyperbolic nanogroove metasurface serves as an enhanced plasmonic sensing platform for engineering light–matter interactions. Phase‐related Goos–Hänchen shift shows a high sensitivity to analyte presence under plasmonic resonance effect. The detection limit is 0.1 × 10 −18 m for bovine serum albumin molecule and below 1 × 10 −15 m for biotin molecule with the nanogroove metasurface‐based sensor.